Manufacture of banana powder - Deang, Amado (College of Engineering, 1989)
The plant location we thought suitable for our purpose is Davao City. Here, supply of bananas is speedy and plentiful. There is also a dependable supply of water, and adequate power supply. Sewage disposal facilities are available, and so is transportation. Even manpower is not a problem; it is even on the cheap side. This plant designed to manufacture banana powder from ripe Cavendish bananas through the use of spray drier has a capacity of 517 kg/day, with a profit of P14 kg and an annual manufacturing cost of P5,197,800. It has a fixed capital investment of P15,272,490. The breakeven point is at 81,760 kg per year and pay-out time is in 4 years.